The neurodiverse workplace : an employer's guide to managing and working with neurodivergent employees, clients and customers - Honeybourne, Victoria (Language and communication teacher) (Jessica Kingsley Publishers, 2020)
"Estimates suggest that up to 20% of employees, customers and clients might have a neurodivergent condition - such as dyslexia, autism, Asperger's, ADHD or dyspraxia - yet these individuals often struggle to gain and maintain employment, despite being very capable. This practical, authoritative business guide will help managers and employers support neurodiverse staff, and gives advice on how to ensure workplaces are neuro-friendly. The book demonstrates that neurodiversity is a natural aspect of human variation to be expected and accepted, rather than a deficit to be accommodated. Employer responsibilities are highlighted, including the 2010 Equality Act, and a range of strategies and policies are provided, including recruitment advice and the benefits of neurodiverse employees, along with advice on physical environments, interaction and communication, and working with clients and customers. This book is an ideal resource for all employers wanting to support and empower people with specific needs to help create a more inclusive workplace, benefiting both neurodiverse individuals and the companies employing them."--